Simplified sample processing combined with a sensitive one-tube nested PCR assay for detection of Pneumocystis carinii in respiratory specimens. - Mathis, A (1997)
Early diagnosis of Pneumocystis carinii pneumonia, a life-threatening complication in immunosuppressed patients, may lower morbidity and mortality. We have developed a one-tube nested PCR assay for the detection of P. carinii in respiratory specimens. Four primers were selected from the sequence of the small-subunit rRNA gene of P. carinii to amplify a 265-bp fragment, and their specificities for P. carinii were confirmed by both theoretical evaluations (by computer-assisted comparison with the sequences in GenBank) and empirical evaluations (with DNA from medically important fungi and diagnostic samples). The assay was optimized for routine diagnostic use. Processing of the clinical samples is rapid and simple (digestion with proteinase K directly in PCR buffer at room temperature in the presence of 10% Chelex 100 and no further purification steps). Bovine serum albumin (1 mg/ml) and glycerol (10%) in the amplification buffer reduced the number of samples inhibitory to the PCR, as assessed by control reactions containing a size-modified target. A total of 749 clinical specimens (312 bronchoalveolar lavage, 403 sputum or induced sputum, and 34 other specimens) from 507 patients (295 human immunodeficiency virus [HIV]-infected and 164 non-HIV-infected patients and 48 patients whose HIV status was unknown) were tested by PCR, and the results were compared with those of an indirect immunofluorescence assay (IFA). Concordant results were obtained for 732 samples (646 negative and 86 positive). There were 17 discrepant results: 12 were PCR positive and IFA negative, and 5 were PCR negative and IFA positive. After resolution of the discrepant results by review of the patients' clinical data, the sensitivity and specificity were 94.8 and 99.1%, respectively, for PCR and 93.8 and 100%, respectively, for IFA. In conclusion, the short procedure time and the technical ease of this PCR assay render it suitable for implementation in routine diagnostic laboratories.